Effect of Panicle Morphology on Grain Filling and Rice Yield: Genetic Control and Molecular Regulation - Parida, Ajay Kumar; Sekhar, Sudhanshu; Panda, Binay Bhushan; Sahu, Gyanasri; Shaw, Birendra Prasad (Frontiers in Genetics, 2022)
The demand for rice is likely to increase approximately 1.5 times by the year 2050. In contrast, the rice production is stagnant since last decade, as the ongoing rice breeding programme is unable to increase the production further, primarily because of the problem in grain filling. Investigations have revealed several reasons for poor filling of the grains in the inferior spikelets of the compact-panicle, which are otherwise genetically competent to develop into well-filled grains. Among these, the important being 1) poor activities of the starch biosynthesizing enzymes, 2) high ethylene production leading to inhibition in expressions of the starch biosynthesizing enzymes, 3) insufficient division of the endosperm cells and endoreduplication of their nuclei, 4) low accumulation of cytokinins and IAA that promote grain filling, and 5) altered expressions of the miRNAs unfavourable for grain-filling. At the genetic level, several genes/QTLs linked to the yield traits have been identified, but the information so far has not been put into perspective towards increasing the rice production. Keeping in view the genetic competency of the inferior spikelets to develop into well-filled grains, and based on the findings from the recent researches, improving grain filling in these spikelets seems plausible through the following biotechnological interventions: 1) spikelet-specific knockdown of the genes involved in ethylene synthesis and overexpression of -CAS (-cyanoalanine) for enhanced scavenging of CN- formed as a by-product of ethylene biosynthesis; 2) designing molecular means for increased accumulation of cytokinins, ABA and IAA in the caryopses; 3) manipulation of expression of the transcription factors like MYC and OsbZIP58 to drive the expression of the starch biosynthesizing enzymes; 4) spikelet-specific over-expression of the cyclins like CycB;1 and CycH;1 for promoting endosperm cell division; 5) targeted increase in accumulation of ABA in the straw during the grain filling stage for increased carbon resource remobilization to the grains. Identification of genes determining panicle compactness could also lead to increase in rice yield through conversion of a compact-panicle into a lax/open one. These efforts have ability to increase rice production by as much as 30%, which could be more than set production target by the year 2050.